ANALISIS STRUKTUR MODAL DAN RASIO HUTANG TERHADAP KINERJA KEUANGAN DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Khotimah, Khusnul; Harahap, Muhammad Nasim (Economic Education, University of Jember, 2024)
This study examines debt ratios also capital structure that can affect financial performance through company size which is used as a moderating variable. The classic assumption test with Moderated Regression Analysis (MRA) is the analytical method used. The research method used was purposive sampling. Ten pharmaceutical companies written on the IDX between 2019-2022 period became observational data according to this study. The findings of this research state that financial performance is significantly also negatively affected by capital structure because companies decide to use external funds to carry out investment and operational activities. Meanwhile, financial performance is significantly and negatively affected by the debt ratio because the high level of liabilities makes the company increasingly unable to pay its obligations or debts due to high debt interest. Furthermore, the results of this research also indicate that company size is not able to moderate capital structure on financial performance because a firm's capital structure may be utilized as a source of corporate finance, although company size does not always imply a growth in it. Meanwhile, the debt ratio cannot be moderated by company size on financial performance because the larger the company size does not affect the debt ratio.